Stem cells patents: main features and citation analysis - Bochi, Fernanda [UNESP]; Mielniczuk Moura, Ana Maria (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2020)
This is a quantitative, patentometric, descriptive study that makes use of production and citation indicators to achieve specific purposes. Based on Price's square root law, the 181 most cited patents in the area of stem cells were the object of this study. After the collection of patents, information was extracted so that it could meet specific objectives, such as priority number, international patent classification, non-patent citation, and patent citation. It has been found that 80% of patents are from US-based companies; 6.7% are based in Japan; 3.6% in England, about 2% in France and Switzerland; 1.2% in Denmark and Ireland, and the others (3.3%) are distributed among companies in the Netherlands, Austria, Germany, China and Canada. Regarding the International Patent Classification (IPC), the patents of this research were classified into 5 sections, of which the area of human needs outstanded with 52.51%. The 181 patents found performed a total of 6,970 citations to other patents, of which 84 were the most cited. The patents that received the highest number of citations were US5486359-A and US6200806-B1, with 40 occurrences (0.26%), both filed in the US office. A hundred forty one out of the 181 patents cited non-patent documents (CR field). It was observed that, based on what could be identified, most citations of non-patent documents are citations of scientific journals (1,426), totaling 7,701 articles cited (+/- 5.5 articles/journal). Patent documents contain important information for understanding the development of science and technology. It is concluded that patents are important sources to be analyzed and that more detailed studies of what is cited in patents should be carried out.
Keywords: Patents; Stem cells; Patentometrics; Citation Analysis